Radiological analysis for radioactivity depth distribution in activated concrete using gamma-ray spectrometry. (March 2021) - Lee, Byungchae; Kim, Yonguhn; L'yi, Wonsik; Kim, Junha; Seo, Bumkyung; Hong, Sangbum
Abstract: In this research, in-situ measurement methods to analyze the radioactivity depth distribution were developed by measuring 152 Eu emitted from activated concrete used the Peak to Compton (PTC) method using a high-purity germanium (HPGe) detector. The experimental results of various radioactivity depth distributions agree within 3% relative error with the results of an MCNP simulation. The correlation between the values obtained with the PTC method and the radioactivity depth distribution was derived. In order to use the PTC method in the field, the impact of the material composition, surface area, and density change of the measurement target was evaluated by an MCNP simulation. The developed method was applied to activated concrete in cyclotron facilities and the results were compared with the sample analysis, revealing a relative error of less than 20%. The results of this research will be useful in quickly and accurately evaluating the radioactivity depth distribution of activated concrete. Further study should be carried out in order to enable analysis of various forms of radioactivity depth distributions of activated structures in nuclear facilities. Highlights: Radiological Analysis for radioactivity depth distribution in activated concrete. In situ gamma spectrometric measurement of 152Eu. Gamma-ray spectrometry based Peak to Compton method is proposed for radioactivity depth distribution analysis. Field applicability evluation of activated concrete.